Macrophages in Health and Non-Infectious Disease 2.0 - Evgeny E. Bezsonov; Alexei Gratchev; Alexander N. Orekhov (Biomedicines, 2022)
This Special Issue (SI) has collected the most recent publications on the mechanisms that macrophages use to regulate homeostasis and their involvement in the pathogenesis of various non-infectious diseases [...]